Acceptance Mechanism of Unspecified Time Workers at PT. Surya Agro Persada based on Applicable Law - Burhayan Burhayan (Syntax Corporation Indonesia, 2023)
If the worker has undergone a Certain Time Work Agreement (PKWT) 2 times and an extension of 1 time, on the basis of the evaluation of the worker who is assessed by his supervisor or the head of the department to be eligible, it can be proposed to become an Indefinite Time Work Agreement or in other terms, namely Permanent Workers. In this study, the author uses a type of research, namely empirical juridical, namely by collecting primary and secondary data in the library then continued with field research (field rescarch) to collect primary data directly from the community. The results of this study concluded that the Indefinite Time Worker Acceptance Mechanism Applicants who apply for leadership positions can directly at PT. Surya Agro Persada which directly becomes PKWTT and Selection decision The decision by the direct supervisor or by the Human Resources Department on the decision to accept workers marks the end of the selection process. Decisions are usually submitted by phone, the company's official website or by e-mail. After the decision is received, the prospective workforce will be accepted as workers. The employment agreement is regulated in Law Number 13 of 2003 concerning employment. Article 1 number 14 work agreement as an agreement between labor workers and employers or employers who have work conditions, rights, and obligations of the parties. Indefinite Time Work Agreement (PKWTT) is an agreement between workers and employers, where the period is not specified either in the agreement, law or custom, or occurs legally due to the employer's violation of legal provisions.